Development of Emotional Intelligence as a Component of Successful Marketing Training (Economics and region, 2019)
The problem of development of emotional intelligence of successful training of marketers in the conditions of competitive environment is considered. The purpose of the research is defined and revealed, namely: peculiarities of students' emotional state and influence on learning; developing greater awareness of the importance of EQ in training marketing professionals. As a result of the empirical study according to the method of N. Hall, the average level of EQ was found in the majority of respondents.
Keywords: emotional intelligence; emotional balance; social prevention; personal identity